2022
DOI: 10.1039/d2sc01826h
|View full text |Cite
|
Sign up to set email alerts
|

Probing longitudinal carrier transport in perovskite thin films via modified transient reflection spectroscopy

Abstract: An accurate characterization on the longitudinal (along the thickness direction) carrier transport property is of significant importance for evaluating the quality and performance of perovskite thin films. Herein, we report...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The absorption spectra were fitted by the Elliott's model (Figure S2, Supporting Information) to separate contributions from exciton absorption and continuum absorption. [ 36 ] The exciton binding energies ( E B ) and bandgaps ( E g ) are extracted and determined to be E B = 19.0 meV and E g = 2.25 eV for MAPbBr 3 , and E B = 25.7 meV and E g = 2.21 eV for MAPbBr 3− x I x . The bandgap of MAPbBr 3− x I x is slightly smaller than that of MAPbBr 3 , and the enhanced light absorption platform of MAPbBr 3− x I x between 600 and 800 nm may be ascribed to the surface‐adsorbed iodine on the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…The absorption spectra were fitted by the Elliott's model (Figure S2, Supporting Information) to separate contributions from exciton absorption and continuum absorption. [ 36 ] The exciton binding energies ( E B ) and bandgaps ( E g ) are extracted and determined to be E B = 19.0 meV and E g = 2.25 eV for MAPbBr 3 , and E B = 25.7 meV and E g = 2.21 eV for MAPbBr 3− x I x . The bandgap of MAPbBr 3− x I x is slightly smaller than that of MAPbBr 3 , and the enhanced light absorption platform of MAPbBr 3− x I x between 600 and 800 nm may be ascribed to the surface‐adsorbed iodine on the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…While the interpretation of film TA responses is more complex than that of solutions, the fact that the response is affected by the change in the refractive index opens new opportunities. One of them is the possibility to monitor the change in carrier distribution across the sample. In traditional TA measurements, the photoinduced change of the sample absorbance depends on the total number of the excited states or the photocarriers but does not depend on carrier distribution in the sample . On the contrary, in films, reflection from the sample surface depends on the refractive index change at the surface (or the surface carrier density) rather than the total number of carriers in the sample.…”
Section: Effect Of Carrier Distribution and Diffusionmentioning
confidence: 99%
“…TR spectroscopy technique, enabling the direct observation and quantification of longitudinal carrier transport within polycrystalline MAPbI 3 films. 35 By the back-exc. TR method, the dynamics of carrier transport along the thickness direction are addressed by spatially separating the pump (excitation) and probe beams on opposite sides of the film (Figure 3c), thereby directly capturing the longitudinal charge transfer from the excitation side to the probe side (Figure 3d).…”
Section: Carrier Diffusion and Surface Recombinationmentioning
confidence: 99%
“…On this basis, Zhao et al have reported the development of a modified back-excitation (back-exc.) TR spectroscopy technique, enabling the direct observation and quantification of longitudinal carrier transport within polycrystalline MAPbI 3 films . By the back-exc.…”
Section: Time-resolved Spectroscopy For Carrier Transport Studymentioning
confidence: 99%
See 1 more Smart Citation